The STOP project. (30th September 2020) - Sassi, F
Abstract: The STOP project aims at expanding and consolidating the multi-disciplinary evidence base upon which effective and sustainable policies can be built to prevent and manage childhood obesity. STOP also aims at creating the conditions for evidence to translate into policy and for policy to translate into impacts on the ground. The primary focus of STOP is on the cumulative impacts of multiple and synergistic exposures in vulnerable and socially disadvantaged children and their families, which must be a priority target for the fight against childhood obesity in Europe to reach a tipping point and succeed. STOP will identify critical stages in childhood at which interventions can be most effective and efficient. STOP is covering the whole umbrella of different research disciplines, to be able to understand and produce useful policy recommendations for complex issues such as childhood obesity. It is providing basic clinic research insights, comprehensive epidemiological data, study and overview of different public health-oriented measurements, understanding of stakeholders networking and effective communication. It builds on the observation that many interventions deployed by governments have failed to improve health-related behaviours in a sustained way over the life cycle. Little has been done to combine and triangulate different sources of biological, socio-economic and behavioural data to look at the overall, long-term consequences of an intervention on nutrition and metabolic health. Therefore, among other things, STOP focuses on the core idea that obesity has multiple and diverse characterisations, and therefore that one-size-fits-all policy approaches to childhood obesity are bound to fail, and the scientific component of the project is designed to recognise diversity and support the development of tailored solutions.